Barbados : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This report reviews economic developments in Barbados during the 1990s. To stem the economic decline, in April 1991, the government tightened fiscal policy. Measures were announced to cut the central government overall deficit from 7.3 percent of GDP in 1990/91 to about 3 percent of GDP in 1991/92, including increases in taxation and fees and cutbacks in current and capital expenditure. However, the measures were insufficient, especially since they were not supported by a tightening of other policies, and economic performance continued to deteriorate in the first half of 1991/92.